Hindsight is 20/20 Vision: What International Students Wished They Had Known Before Coming to Live and Learn in Ireland - Farrelly, Tom; Murphy, Tony (Journal of International Students, 2018)
This article reports on a survey (n=573) of international students who were attending one of a group of five higher education institutes (HEIs) in the south of Ireland. This study sought to identify what knowledge these students had about their host country before coming to Ireland. In this study, we also attempted to identify what aspects of living and learning in Ireland these students wished they had known about before they left their home countries. Finally, we discuss the types of academic, socio-cultural and practical resources that both welcoming colleges and international students should consider prioritising before departure, so as to truly help the transition from a home to host country.